Resinicization and Digital Citizenship in Hong Kong: Youth, Cyberspace, and Claims-Making - Adorjan, Michael; Yau, Ho Lun (Qualitative Sociology Review, 2015)
Under the “one country, two systems” model fashioned after its handover to China in 1997, Hong Kong, a Special Administrative Region of China, is to retain its rule of law, capitalist system, and accompanying political and ideological independence. However, tensions remain centered on concerns held by many Hong Kong citizens over the “resinicization” of Hong Kong, related to anxieties regarding the putative erosion of political and ideological freedoms. This paper examines the claims-making of the student activist group Scholarism, who effectively used Facebook to raise awareness of and successfully resist a government proposal to introduce a national education curriculum into Hong Kong schools. Scholarism’s resistance and ability to mobilize mass demonstrations against the government is significant considering the lack of democratic channels in Hong Kong. Implications are explored for the examination of how claims-making in cyberspace impacts the social problems process, especially in non-democratic and post-colonial contexts.